Diverse Functions of Small RNAs in Different Plant–Pathogen Communications - Huang, Juan; Yang, Meiling; Lu, Lu; Zhang, Xiaoming (Frontiers in Microbiology, 2016)
RNA silencing is a conserved mechanism that utilizes small RNAs (sRNAs) to direct the regulation of gene expression at the transcriptional or post-transcriptional level. Plants utilizing RNA silencing machinery to defend pathogen attack was first identified in plant-virus interaction and later was observed in distinct plant-pathogen interactions. RNA silencing is not only response for suppressing RNA accumulation and movement of viral and viroid, but also response for facilitating plant immune responses to defend against bacterial, oomycete, and fungal pathogen attack. Interestingly, even the same plant sRNA can perform different roles during encounters with different pathogens. On the other side, pathogens counteract by generating sRNAs that directly regulate pathogen gene expression to increase virulence and also sRNAs that target host genes to facilitate pathogen infection. Here, we summarize the current knowledge of the characterization and biogenesis of host- and pathogen-derived sRNAs, particularly the different RNA silencing machineries that plants utilize to defend against different pathogens. The functions of these sRNAs in defense and counter-defense and their mechanisms for regulation during different plant-pathogen interactions are also discussed.